Association of substance dependence phenotypes in the COGA sample. (16th May 2014) - Wetherill, Leah; Agrawal, Arpana; Kapoor, Manav; Bertelsen, Sarah; Bierut, Laura J.; Brooks, Andrew; Dick, Danielle; Hesselbrock, Michie; Hesselbrock, Victor; Koller, Daniel L.; Le, Nhung; Nurnberger, John I.; et al.
Abstract Alcohol and drug use disorders are individually heritable (50%). Twin studies indicate that alcohol and substance use disorders share common genetic influences, and therefore may represent a more heritable form of addiction and thus be more powerful for genetic studies. This study utilized data from 2322 subjects from 118 European‐American families in the Collaborative Study on the Genetics of Alcoholism sample to conduct genome‐wide association analysis of a binary and a continuous index of general substance dependence liability. The binary phenotype (ANYDEP) was based on meeting lifetime criteria for any DSM‐IV dependence on alcohol, cannabis, cocaine or opioids. The quantitative trait (QUANTDEP) was constructed from factor analysis based on endorsement across the seven DSM‐IV criteria for each of the four substances. Heritability was estimated to be 54% for ANYDEP and 86% for QUANTDEP. One single‐nucleotide polymorphism (SNP), rs2952621 in the uncharacterized gene LOC151121 on chromosome 2, was associated with ANYDEP (P = 1.8 × 10−8), with support from surrounding imputed SNPs and replication in an independent sample [Study of Addiction: Genetics and Environment (SAGE); P = 0.02]. One SNP, rs2567261 in ARHGAP28 (Rho GTPase‐activating protein 28), was associated with QUANTDEP (P = 3.8 × 10−8), and supported by imputed SNPs in the region, but did not replicate in an independent sample (SAGE; P = 0.29). The results of this study provide evidence that there are common variants that contribute to the risk for a general liability to substance dependence.